Lorenzo Gambara's Caprarola and On Poetic Composition : Text, Translation and Commentary - Gwynne, Paul G., (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
In 1569, Lorenzo Gambara published a long verse description of the Farnese palace at Caprarola, which was dedicated to Cardinal Alessandro Farnese. Twelve years later, this poem was thoroughly revised and considerably lengthened. In the meantime, the aged poet had repudiated the compositions of his youth and repented his lascivious verse. This dramatic change of heart is documented in a Latin treatise in which poets are encouraged to eschew pagan and classical themes in favor of Christian subject matter. This volume presents the first English translation with commentary of the revised poem and the treatise, which is newly ascribed to the Jesuit polymath Antonio Possevino.